1989
DOI: 10.1007/bf00718607
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of alveolar capillary endothelial cells, alveolar epithelial cells and alveolar macrophages in patients with pulmonary fibrosis, with special reference to MHC class II antigens

Abstract: Major histocompatibility complex (MHC) class II antigens are essential in the presentation of antigens to T lymphocytes, and cells expressing MHC class II antigens are known to play a role as antigen presenting cells (APC). We investigated the distribution of MHC class II antigens and the reactivity of monoclonal antibodies OKM1 and OKM5 in normal and fibrotic lungs immunohistochemically. The results showed that alveolar capillary endothelial cells (ACEnd) expressed MHC class II antigens and were reactive with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…PnIIs express constitutively MHC class II molecules, 18 and this expression is increased by IFN-␥ in rat 23 or in some pathological conditions in human. 40,41 PnIIs also express cathepsins, 42 CD54, 20 and co-stimulatory molecules such as CD80 and CD86. 43 Therefore, these epithelial cells, strategically localized in the lung at the interface with the outside environment, express many of the molecules required for efficient antigen presentation to CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…PnIIs express constitutively MHC class II molecules, 18 and this expression is increased by IFN-␥ in rat 23 or in some pathological conditions in human. 40,41 PnIIs also express cathepsins, 42 CD54, 20 and co-stimulatory molecules such as CD80 and CD86. 43 Therefore, these epithelial cells, strategically localized in the lung at the interface with the outside environment, express many of the molecules required for efficient antigen presentation to CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…A number of groups have shown that IFN-␥-treated large vessel endothelial cells cause alloproliferation of resting CD4 ϩ T cells in vitro, allowing them to postulate that constitutively HLA class II-positive endothelial cells cause allostimulation of resting T cells in vivo (4 -6). Similarly, human epithelial cells associated with allografts have been shown to be constitutively positive for HLA-DR in vivo (7)(8)(9)(10) and to up-regulate HLA-DR after IFN-␥ stimulation in vitro (11)(12)(13). However, IFN-␥-stimulated epithelial cells do not induce proliferation of allospecific CD4 ϩ T lymphocytes, and may even induce a state of anergy or nonresponsiveness in vitro (14).…”
mentioning
confidence: 99%
“…Then, the indirect HRP-labcled antibody method was applied for immunological re action as previously described [15], Briefly, the procedure involves successive incubations with the first antibodies in optimal dilu tions (rabbit anti-SP antibody 1:600. rabbit anti-CGRP antibody 1:1.200) for 12 It at 4°C, and the second antibody (1:80) for 4 h at 4°C. The antigen-antibody reaction was visualized with 0.25% diaminobenzidinc (DAB) solution containing 0.01 M sodium azide and 0.01 M hydrogen peroxide, and counterstained with methyl green.…”
Section: Immunohistochemistrymentioning
confidence: 99%